ИЛК ЎРТА АСРЛАРДА МАРКАЗИЙ ОСИЁДАГИ ЭТНОСЛАРАРО МАЪНАВИЙ МАДАНИЯТНИНГ ЎЗАРО ТАЪСИРИ (Scientific journal of the Fergana State University, 2023)
The article illustrates the features of interactions and cooperation of the peoples of Central Asia in the field of spiritual culture and cult-religious relations. In particular, the role of these relations in the development of civilization processes during the early Medieval Ages is analyzed; the features of achieving interreligious compromise are disclosed. Special attention is paid to the role of the Sogdian written culture in the aforementioned processes in the early Medieval Ages.